The art of not making the new artist-artisan relationship - Petry, Michael (Thames & Hudson, 2011)
Can an artist claim that an object is a work of art if it has been made for him or her by someone else? If so, who is the author of such a work? And just what is the difference between a work of art and a work of craft? In the first book of its kind, Michael Petry tackles these questions head on.